Infiltrating treg reprogramming in the tumor immune microenvironment and its optimization for immunotherapy - Zhaokai Zhou; Jiaxin Xu; Shutong Liu; Yingying Lv; Ruiqi Zhang; Xing Zhou; Yuyuan Zhang; Siyuan Weng; Hui Xu; Yuhao Ba; Anning Zuo; Xinwei Han; et al. (BMC, 2024)
Abstract Immunotherapy has shown promising anti-tumor effects across various tumors, yet it encounters challenges from the inhibitory tumor immune microenvironment (TIME). Infiltrating regulatory T cells (Tregs) are important contributors to immunosuppressive TIME, limiting tumor immunosurveillance and blocking effective anti-tumor immune responses. Although depletion or inhibition of systemic Tregs enhances the anti-tumor immunity, autoimmune sequelae have diminished expectations for the approach. Herein, we summarize emerging strategies, specifically targeting tumor-infiltrating (TI)-Tregs, that elevate the capacity of organisms to resist tumors by reprogramming their phenotype. The regulatory mechanisms of Treg reprogramming are also discussed as well as how this knowledge could be utilized to develop novel and effective cancer immunotherapies.